An alternative in vitro method for testing the potency of the polyvalent antivenom produced in Costa Rica - Gutiérrez, José María (1988)
The ability of several batches of polyvalent antivenom to neutralize indirect hemolytic activity of Bothrops asper venom was studied using a sensitive plate test. All samples of antivenom tested effectively neutralized this activity. A highly significant correlation was observed between neutralization of indirect hemolysis and neutralization of lethal activity. This simple and sensitive in vitro test could be used to monitor antibody levels in horses immunized to produce polyvalent antivenom.